Expression and Purification of the Full Length and N-Terminal Truncated Variants of Insect CYP6Z2 in the Cytosol of Escherichia Coli for Potential 3D Experimental Studies - Kusimo, Michael Olugbenga; Hama Soor, Taib Ahmed; Adedeji, Ahmed Adebowale (Kurdistan Journal of Applied Research, 2024)
Cytochrome P450 enzymes (P450s) offer innate resistance defence for malaria vectors against the insecticides permitted by WHO to be used in vector control tools. P450s can detoxify broad substrates and simultaneously metabolise them, thus the availability of experimental three-dimensional structures of these key insecticide detoxifiers is vital to improving our knowledge of their enzyme activities. Despite the importance of this family of proteins in insecticide resistance, there are no available experimental three-dimensional structures of insect P450 yet.  For this investigation, a carboxy-terminal Histidine-tagged recombinant CYP6Z2 was heterologously expressed in E. coli to generate a soluble holoprotein suitable for an experimental three-dimensional structure. The expressed enzyme was purified from the cytosol of E. coli via the combination of various purification techniques and cholic acid sodium salt. Two truncated N-terminal signal peptides: short deletion of 11 amino acids and long deletion of 23 amino acids of the hydrophobic domain, were created to prevent aggregation, improve solubility, and facilitate crystallisation. The CYP6Z2 (full length) produced a holoprotein with a P450 protein concentration of 0.60 nmol/mL, whereas the two truncated CYP6Z2 isoforms produced only the inactive species with no peak at 450 nm. We conclude that the hydrophobic signal peptide region of the insect Cytochrome P450s seems sensitive and indispensable to ensuring 3-D folding and stability.